The ER quality control and ER associated degradation machineries are vital for viral pathogenesis - Verchot, Jeanmarie (Frontiers in Plant Science, 2014)
The endoplasmic reticulum (ER) is central to protein production and membrane lipid synthesis. The unfolded protein response (UPR) supports cellular metabolism by ensuring protein quality control in the ER. Most positive strand RNA viruses cause extensive remodeling of membranes and require active membrane synthesis to promote infection. How viruses interact with the cellular machinery controlling membrane metabolism is largely unknown. Furthermore, there is mounting data pointing to the importance of the UPR and ER associated degradation (ERAD) machineries in viral pathogenesis in eukaryotes emerging topic. For many viruses, the UPR is an early event that is essential for persistent infection and benefits virus replication. In addition, many viruses are reported to commandeer ER resident chaperones to contribute to virus replication and intercellular movement. In particular, calreticulin, the ubiquitin machinery, and the 26S proteasome are most commonly identified components of the UPR and ERAD machinery that also regulate virus infection. In addition, researchers have noted a link between UPR and autophagy. It is well accepted that positive strand RNA viruses use autophagic membranes as scaffolds to support replication and assembly. However this topic has yet to be explored using plant viruses. The goal of research on this topic is to uncover how viruses interact with this ER-related machinery and to use this information for designing novel strategies to boost immune responses to virus infection.